2013
DOI: 10.1038/cr.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

A role for the RNA-binding protein MOS2 in microRNA maturation in Arabidopsis

Abstract: microRNAs (miRNAs) play important roles in the regulation of gene expression. In Arabidopsis, mature miRNAs are processed from primary miRNA transcripts (pri-miRNAs) by nuclear HYL1/SE/DCL1 complexes that form Dicing bodies (D-bodies). Here we report that an RNA-binding protein MOS2 binds to pri-miRNAs and is involved in efficient processing of pri-miRNAs. MOS2 does not interact with HYL1, SE, and DCL1 and is not localized in Dbodies. Interestingly, in the absence of MOS2, the recruitment of pri-miRNAs by HYL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
86
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 52 publications
0
86
0
Order By: Relevance
“…The interaction of MAC3A/B with the DCL1 complex also prompted us to test the effect of 299 mac3a mac3b on the formation of the D-body. We crossed a HYL1-YFP transgenic line, which 300 has been used as a reporter for the D-body Wu et al, 2013;Qiao et al, 2015), 301 into mac3a mac3b and examined the percentage of cells containing D-bodies in the root tips and 302 elongation region. As previously reported (Wu et al, 2013), the HYL1-containing D-bodies 303 existed in most cells (~ 84%, Figure 6A, 6B and Supplemental Figure 6A Because MAC3A has considerable sequence difference from MAC3B, we tested if it is a 318 ubiquitin E3 ligase using MBP-MAC3A (Supplemental Figure 5A).…”
Section: Mac3a Binds Pri-mirnas In Vivo 274mentioning
confidence: 99%
“…The interaction of MAC3A/B with the DCL1 complex also prompted us to test the effect of 299 mac3a mac3b on the formation of the D-body. We crossed a HYL1-YFP transgenic line, which 300 has been used as a reporter for the D-body Wu et al, 2013;Qiao et al, 2015), 301 into mac3a mac3b and examined the percentage of cells containing D-bodies in the root tips and 302 elongation region. As previously reported (Wu et al, 2013), the HYL1-containing D-bodies 303 existed in most cells (~ 84%, Figure 6A, 6B and Supplemental Figure 6A Because MAC3A has considerable sequence difference from MAC3B, we tested if it is a 318 ubiquitin E3 ligase using MBP-MAC3A (Supplemental Figure 5A).…”
Section: Mac3a Binds Pri-mirnas In Vivo 274mentioning
confidence: 99%
“…Four other proteins, DAWDLE (DDL; an RNA binding protein), Cap-binding protein 20, Cap-binding protein 80, and NOT2, which are associated with the DCL1 complex (8,(20)(21)(22), also function in miRNA biogenesis. Recent studies also reveal that the correct localization of DCL1 requires NOT2 and MODIFIER OF SNC1, 2 (an RNA binding protein) (8,23). In addition, the accumulation of a subset of miRNAs requires a proline-rich protein named SICKLE (24).…”
mentioning
confidence: 99%
“…7 Several miRNAs have been shown to be involved in antibacterial resistance. 8,9 The function of MOS2 in defense may be partly explained by its role in miRNA maturation.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…Recently it was further shown that MOS2 is involved in micro RNA (miRNA) maturation by binding to long primary miRNA (pri-miRNA) transcripts and facilitating their recruitment to HYL1, a protein that assists in the production of miRNAs through the cleavage of pri-miRNA. 7 However, how miRNA maturation affects snc1-mediated autoimmunty is unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation